Creative ethnicity: music as an element of ethnicity among Polish Tatars - Abłażewicz-Górnicka, Urszula; Radłowska, Karolina (Creativity Studies, 2021)
The aim of this article is to analyse the role of ethnic music in the life of the Tatar minority in Poland as an example of creative ethnicity. On the one hand, modern Tatar musical practices construct an interesting example of “invented tradition” because the studied group does not have “musical memory”, while on the other hand, these activities are aimed at the group’s future. Music can fulfill different social functions. In the case of ethnic groups, three of these functions seem to be particularly relevant: integrational, political (ideological) and identity. Desk research reveals the formal and informal musical practices undertaken by Polish Tatars. The values and musical assets associated with Tatar culture reflect the minority’s identity. The main statement of the article is that music is an important element that contributes to constructing the contemporary group’s identity. Tatar music is becoming an essential element of Tatar culture, enhancing a sense of the group’s distinctiveness. The contemporary Tatar music groups construct a significant Tatar showcase to the audience outside of the Tatar ethnic group, as well as form an important identity element of the Tatar community and a manifestation of creative ethnicity. It is also possible to find correlations between their repertoire and contemporary group transformations, including those related to its identity.